Implementasi Modul Ajar “Menerapkan Nilai Pengampunan Dalam Kehidupan” Pada Pembelajaran PAK Di Kelas X SMA Negeri 3 Palangkaraya - Jen Katrin Enok; Nita Natalia; Martisia Fensia; Matius Timan Herdi Ginting (Educational Journal, 2026)
This study aims to describe the implementation of the teaching module “Applying the Value of Forgiveness in Daily Life” in Christian Religious and Character Education learning for tenth-grade students at SMA Negeri 3 Palangkaraya. The implementation was based on the Merdeka Curriculum, which emphasizes character building and competency development through meaningful learning experiences. The learning process applied the Contextual Teaching and Learning (CTL) approach, involving group discussions, case study analysis, presentations, and reflection activities. Data were collected through observations of student participation, analysis of group work results, and project assessments. The findings reveal that 85% of students actively participated in the learning process, all groups successfully completed the assigned tasks, and assessment results showed 34 students categorized as “good” and 15 as “sufficient.” Learning media such as reflective videos and case studies effectively enhanced students’ understanding of the value of forgiveness. Challenges identified in the implementation included limited time for deep reflection and the reluctance of some students to share personal conflict experiences. The study concludes that the implementation of a forgiveness-based teaching module is effective in fostering empathy, conflict management skills, and mutual respect among students